Epidemiology and treatment options for ophthalmic complications of mucosinequiant diseases - Yey Fano Machín (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: mucosinequiant diseases are those that affect skin and mucosa with blister-vesicular wounds, they are usually bilateral and are characterized by distorting the conjunctival anatomy, eyelids, lachrymal way and that universally lead to a dry keratoconjunctivitis.Objective: to update epidemiological issues and treatment options for ophthalmic complications of mucosinequiant diseases Material and Methods: a literature review on conceptual issues, classification, etiopathology, epidemiology, clinical manifestation, complications and treatment of mucosinequiant ophthalmological diseases available in hard copies and digital support was made. To search, we used electronic databases such as PubMed, Central BioMed and SCIELO, extending over several years to the present. We deal with diseases such as trachoma, cicatricial pemphigoid, Stevens-Johnson syndrome and woody conjunctivitis, because mucosinequiant diseases are those which present greater conjunctival compromise. Results: mucosinequiant cause conjunctival cicatrization and serious ophthalmologic complications that could compromise vision up to blindness. Conclusions: mucosinequiant diseases are a frequent cause of ocular morbidity causing severe damage to the ocular surface. The use of amniotic membrane graft, oral mucosa and corneal conjunctival limbus stem cell transplant are used options with good results in the treatment of ophthalmic complications of these diseases. Keywords: Trachoma, cicatricial pemphigoid, Stevens-Johnson syndrome, woody conjunctivitis, amniotic membrane, ocular surface, mucosinequiant diseases